Inovasi Media Ular Tangga Edukasi Islami dalam Pembelajaran Fikih Materi Shalat - Muriha, Mazya; Pratiwi, Ratna; Fahreza, Muhammad Ahyar; Sholikhah, Ika Wahdina; Putranta, Himawan (Universitas Pendidikan Indonesia, 2025)
AbstractFiqh learning at the elementary school (SD/MI) level is often perceived as monotonous and lacking active student engagement. This study aims to develop and evaluate the feasibility of an interactive learning medium called Islamic Educational Snakes and Ladders, focusing on the topic of prayer (salat). The research employed a Research and Development (RD) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation was conducted by four experts using a feasibility assessment instrument, and the data were analyzed using descriptive quantitative methods. The results showed that the medium achieved a feasibility score of 92.56%, categorized as highly feasible. The medium consists of a game board, educational cards (knowledge, practice, and wisdom), player tokens, dice, and a play guide designed to promote active learning. These findings indicate that the Islamic Educational Snakes and Ladders medium has the potential to enhance students’ understanding and interest in fiqh, particularly in the area of prayer. However, the study is limited by the absence of direct effectiveness testing on students. Therefore, further research is recommended to empirically examine the impact of this medium on learning outcomes through experimental or longitudinal study designs.Keywords: Learning media, Islamic educational snakes and ladders, Fiqh, elementary school (SD/MI), Research and DevelopmentAbstrakPembelajaran fikih di tingkat SD/MI kerap dianggap monoton dan kurang melibatkan siswa secara aktif. Penelitian ini bertujuan untuk mengembangkan dan menguji kelayakan media pembelajaran interaktif berupa Ular Tangga Edukasi Islami pada materi ibadah salat. Metode yang digunakan adalah Research and Development (RD) dengan model ADDIE, meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Validasi dilakukan oleh empat ahli menggunakan lembar penilaian kelayakan, dan data dianalisis secara deskriptif kuantitatif. Hasil menunjukkan bahwa media memperoleh skor kelayakan sebesar 92,56%, termasuk kategori sangat layak. Media terdiri dari papan permainan, kartu edukatif (ilmu, amal, dan hikmah), pion, dadu, serta panduan bermain yang dirancang untuk mendukung pembelajaran aktif. Temuan ini menunjukkan bahwa media Ular Tangga Edukasi Islami berpotensi meningkatkan pemahaman dan minat belajar peserta didik terhadap materi fikih, khususnya ibadah salat. Keterbatasan penelitian ini terletak pada belum dilakukannya uji efektivitas secara langsung terhadap peserta didik. Oleh karena itu, penelitian lanjutan disarankan untuk menguji dampak penggunaan media ini terhadap hasil belajar secara empiris melalui desain eksperimen atau studi longitudinal. Kata kunci : Media pembelajaran, Ular tangga edukasi Islami, Fiqih, SD/MI, Research and Development